Nickel-cobalt hydroxide supercapacitor composite electrode and preparation method and application thereof

By electrodeposition in ionic liquid and in situ electrochemical activation, a high load and high magnification nickel-cobalt hydroxide supercapacitor composite electrode was prepared, which solved the energy density and cycle stability of the electrode material in the prior art. The problem of insufficient results enables high-performance supercapacitor electrode materials.

CN119296988APending Publication Date: 2025-01-10KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411459162.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials have constraints in terms of high load capacity and high rate performance, resulting in insufficient energy density and cycling stability, making it difficult to meet the needs of large-scale applications.

Method used

Nicocoal hydroxide (NiCo(OH)2) electrode is prepared by electrodeposition in ionic liquid, and converted into NiCo(OH)2/NiCoOOH composite electrode through in-situ electrochemical activation, combined with graphite sheets or carbon paper as conductive Matrix, electrodeposition and activation treatment using specific expansion fluids and electrolytes.

Benefits of technology

Supercapacitor composite electrodes with high load capacity, high area capacity and high rate performance have been achieved, which significantly improves the energy storage performance and cycle stability of the electrode materials, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296988A_ABST
    Figure CN119296988A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-cobalt hydroxide supercapacitor composite electrode and a preparation method and application thereof, and the preparation method comprises the following steps: growing a NiCo (OH) 2 electrode on an electrode substrate through electro-deposition, and then converting the NiCo (OH) 2 electrode into a NiCo (OH) 2 / NiCoOOH composite electrode through in-situ electrochemical activation; the electrodeposition electrolyte is obtained by dissolving nickel salt and cobalt salt in ionic liquid. The invention further discloses the nickel-cobalt hydroxide supercapacitor composite electrode prepared by the preparation method and application of the nickel-cobalt hydroxide supercapacitor composite electrode in a supercapacitor. The sample obtained through electrodeposition in the ionic liquid has a larger surface area and a rich pore structure, ion transmission is promoted, the utilization rate of active substances is increased, and the capacity performance of the material is further optimized through electrochemical activation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a nickel-cobalt hydroxide supercapacitor composite electrode and a preparation method and application thereof. Background Art

[0002] In recent years, the demand for energy storage devices in the electronic product market has continued to expand, and the development of new energy storage materials with high power and high energy density has become increasingly important. Supercapacitors have attracted widespread attention from researchers due to their excellent cycle stability and fast charge / discharge capabilities. Currently, the activated carbon electrodes that are widely used cannot meet the needs of large-capacity energy storage due to their low energy density. Transition metal oxides and hydroxides, as typical active materials of pseudocapacitive supercapacitors, have been widely studied because of their rich pseudocapacitive reactions, wide sources of raw materials, and low costs. In particular, nickel and cobalt hydroxides have the advantages of abundant reserves, low cost, and high theoretical specific capacity, and are key research materials in the field of transition metal energy storage.

[0003] Traditional electrode materials are coated on a conductive substrate after being mixed with a conductive agent and a binder in a certain proportion as an active material of a supercapacitor. However, the addition of a conductive agent and a binder will produce non-pseudocapacitive active sites inside the electrode, which is the so-called "dead area", which is not conducive to the transmission of electrons and ions inside the material under high load conditions. Electrodeposition is a simple method for preparing high-load electrode materials, which can effectively regulate the microstructure of deposited active substances. CN105895383A and CN104992847A reported the use of an electrodeposition method in an aqueous solution to prepare nickel-based or nickel-cobalt-based hydroxide materials with good capacity performance. However, the capacity of the above two technical solutions is achieved under extremely low conditions. As the deposition time increases, the capacity performance does not show a linear improvement, and the rate performance decreases significantly, and there is no good solution to improve energy density in large-scale applications. Although the high load will increase the electrode thickness, it also hinders the effective penetration of the electrolyte, limits the rapid diffusion of ions and the full utilization of active substances, thereby reducing the capacitance performance of the material. There is an obvious mutual restriction between the loading amount, rate performance and capacity, which leads to the fact that the material loading is often lower than the commercial application standard (10 mg cm -2 ), which limits large-scale promotion.

[0004] Therefore, how to provide an electrode material with high loading capacity, high area capacity, high rate performance and excellent cycle stability is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a high-loading and high-rate nickel-cobalt hydroxide supercapacitor composite electrode and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode comprises the following steps:

[0008] A nickel cobalt hydroxide (NiCo(OH)2) electrode is grown on an electrode substrate by electrodeposition, and then the NiCo(OH)2 electrode is transformed into a NiCo(OH)2 / NiCoOOH composite electrode by in-situ electrochemical activation;

[0009] The electrolyte used in the electrodeposition process is obtained by mixing and dissolving nickel salt, cobalt salt and water in an ionic liquid.

[0010] Beneficial effects: Mixing water with ionic liquids can not only bring into play the physical and chemical properties of ionic liquids such as wide electrochemical window and high thermal stability, but also greatly reduce the viscosity of ionic liquids and improve their conductivity. High-load NiCo-LDH electrode materials with special structures can be obtained by electrodeposition in the mixed system, which is expected to promote the application of supercapacitor energy storage market.

[0011] Preferably, the electrode substrate comprises one or any combination of graphite sheet, graphite paper, carbon paper or metal substrate;

[0012] The thickness of the electrode substrate is 0.1 to 5.0 mm and the area is 1 to 10 cm 2 .

[0013] Beneficial effects: The conductive substrates such as graphite sheets, graphite paper, carbon paper, etc. used in the present invention can provide more abundant electrochemical active sites for the electrodeposition preparation of high-load NiCo-LDH electrode materials due to their high conductivity and large specific surface area, which helps to further improve the energy storage performance of the electrode materials.

[0014] Preferably, the ionic liquid is one of ethylene glycol-choline chloride (Ethaline), urea-choline chloride (Reline), urea, ethylene glycol, betaine-ethylene glycol or urea-choline chloride-betaine.

[0015] Beneficial effects: Ionic liquids have properties such as wide electrochemical window, good thermal stability, and high conductivity. They can regulate the existence state of metal ions in them, providing a special ion transport environment for the preparation of NiCo-LDH electrode materials that is different from the aqueous solution system, which is conducive to the controllable preparation of target materials.

[0016] Preferably, before the electrodeposition, the electrode substrate is immersed in an expansion liquid for electrochemical expansion.

[0017] The swelling liquid is obtained by mixing tetrabutylammonium bromide and acetonitrile in a ratio of 0.4 g:80 ml;

[0018] The expansion time is 2 to 60 minutes.

[0019] Beneficial effects: The surface area of ​​the expanded graphite matrix is ​​significantly increased, providing more electrochemical active sites for the high loading of active substances during electrodeposition, and increasing the area capacity of the electrode material. At the same time, the high conductivity of the graphite electrode is also conducive to the full wetting of the electrolyte and the diffusion / transmission of ions during the charge and discharge process.

[0020] Preferably, in the electrolyte, the concentration of nickel salt is 0.1 mol / L, and the concentration of cobalt salt is 0.1 mol / L; the volume ratio of water to ionic liquid is 2:(1.5-12); the nickel salt is NiCl2, Ni(NO3)2 or NiSO4; the cobalt salt is CoCl2, Co(NO3)2 or CoSO4.

[0021] Beneficial effects: The nickel salt and cobalt salt added to the ionic liquid are not only applicable to nitrates, but other nickel salts and cobalt salts can also be electrodeposited to obtain high-performance electrode materials.

[0022] Preferably, the temperature of the electrodeposition is 25-100°C, and the deposition charge is 1-150°C.

[0023] Beneficial effects: The temperature regulated during the electrodeposition process is not limited to room temperature. High-load NiCo-LDH electrode materials with excellent electrochemical properties can be obtained in the range of 25 to 100°C. By regulating the amount of deposited charge, NiCo-LDH electrode materials with any load can be prepared, providing more selectivity for the controllable preparation of electrode materials.

[0024] Preferably, the in-situ electrochemical activation is performed by CV cycling at a potential of -0.5 to 1.0 V with a scan rate of 10 to 100 mVs -1 , the number of cycles is 1 to 100.

[0025] Beneficial effects: Under the above conditions, electrochemical activation converts Ni / Co(OH)2 into Ni / CoOOH composite film, which greatly improves the capacitance of the electrode material.

[0026] A method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode provides a nickel-cobalt hydroxide supercapacitor composite electrode.

[0027] The invention discloses an application of a nickel-cobalt hydroxide supercapacitor composite electrode in a supercapacitor.

[0028] Beneficial effects: When the composite electrode obtained by the present invention is used as an electrode of a supercapacitor, it simultaneously exhibits high area capacity, excellent rate performance and long-term cycle stability.

[0029] Compared with the prior art, the present invention has the following advantages and technical effects:

[0030] The sample obtained by electrodeposition in the ionic liquid of the present invention has a larger surface area and a rich pore structure, which is helpful to promote ion transmission and improve the utilization rate of active substances, and further optimizes the material capacity performance through electrochemical activation. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0032] Figure 1 It is a flow chart of electrodeposition and activation in an example of the present invention;

[0033] Figure 2 is the XRD pattern of Example 1 in the present invention;

[0034] Figure 3 The SEM images (ab) and elemental mapping diagram (c) of NiCo-LDH in Example 1 of the present invention at different magnifications, and the SEM images (de) and elemental mapping diagram (f) of NiCo-LDH / NiCoOOH at different magnifications;

[0035] Figure 4 This is the GCD diagram of Example 2 of the present invention at different current densities;

[0036] Figure 5 This is a rate performance diagram of Example 3 of the present invention;

[0037] Figure 6 This is a capacity performance diagram of Example 4 of the present invention at different load amounts and different current densities;

[0038] Figure 7 This is a graph of the capacity retention rate of Example 5 in the present invention after 12,000 cycles of charge and discharge at a current density of 200 mA. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] The embodiment of the present invention provides a method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode, comprising the following steps:

[0042] A nickel cobalt hydroxide (NiCo(OH)2) electrode is grown on an electrode substrate by electrodeposition, and then the NiCo(OH)2 electrode is transformed into a NiCo(OH)2 / NiCoOOH composite electrode by in-situ electrochemical activation;

[0043] The electrolyte used in the electrodeposition process is obtained by mixing and dissolving nickel salt, cobalt salt and water in an ionic liquid.

[0044] In a preferred embodiment, the electrode substrate comprises one or any combination of graphite sheet, graphite paper, carbon paper or metal substrate;

[0045] The thickness of the electrode substrate is 0.1 to 5.0 mm and the area is 1 to 10 cm 2 .

[0046] In a preferred embodiment, the ionic liquid is one of ethylene glycol-choline chloride (Ethaline), urea-choline chloride (Reline), urea, ethylene glycol, betaine-ethylene glycol or urea-choline chloride-betaine.

[0047] In a preferred embodiment, the electrode substrate is immersed in a swelling liquid for swelling before the electrodeposition.

[0048] In a preferred embodiment, the swelling liquid is obtained by mixing tetrabutylammonium bromide and acetonitrile in a ratio of 0.4 g:80 ml;

[0049] The expansion time is 2 to 60 minutes.

[0050] In a preferred embodiment, in the electrolyte, the concentration of nickel salt is 0.1 mol / L, the concentration of cobalt salt is 0.1 mol / L; the volume ratio of water to ionic liquid is 2:(1.5-12);

[0051] The nickel salt is NiCl2, Ni(NO3)2 or NiSO4;

[0052] The cobalt salt is CoCl2, Co(NO3)2 or CoSO4.

[0053] In a preferred embodiment, the electrodeposition temperature is 25-100°C, and the deposition charge is 1-150°C.

[0054] In a preferred embodiment, the in-situ electrochemical activation is performed by CV cycling at a potential of -0.5 to 1.0 V with a scan rate of 10 to 100 mVs -1 , the number of cycles is 1 to 100.

[0055] The embodiment of the present invention also provides a method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode and a nickel-cobalt hydroxide supercapacitor composite electrode prepared therefrom.

[0056] The embodiment of the present invention also provides an application of a nickel-cobalt hydroxide supercapacitor composite electrode in a supercapacitor.

[0057] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0058] The room temperature or normal temperature described in the embodiments of the present invention refers to 25±3°C.

[0059] Example 1

[0060] A method for preparing a high-load and high-rate nickel-cobalt hydroxide supercapacitor composite electrode using a eutectic ionic liquid, specifically comprising the following steps:

[0061] (1) mixing choline chloride and ethylene glycol in a molar ratio of 1:2 and stirring at 80° C. for 24 hours to obtain an ionic liquid;

[0062] (2) Weigh Ni(NO3)2 and Co(NO3)2 and dissolve them in 50 mL of the prepared ionic liquid so that the concentrations of Ni(NO3)2 and Co(NO3)2 are 0.1 mol / L, respectively. Then, add 20 mL of deionized water and stir until completely dissolved to obtain an electrolyte;

[0063] (3) Cut the 1mm thick graphite paper into 3×5cm pieces 2 size, and then cleaned with anhydrous ethanol to obtain a graphite electrode for use;

[0064] (4) Weigh 0.4 g of tetrabutylammonium bromide and 80 ml of acetonitrile to prepare an electrode expansion solution, and then place the graphite electrode obtained in step (3) into the electrode expansion solution to expand for 10 minutes, then immerse it in deionized water for cleaning, and then dry it naturally to obtain an expanded electrode;

[0065] (5) placing the expanded electrode obtained in step (4) into the electrolyte obtained in step (2) for electrodeposition, using two parallel graphite sheets as counter electrodes, the expanded electrode as the cathode, and the reference electrode as Ag / AgCl, at room temperature and at a constant voltage of -0.8 V to obtain a NiCo(OH)2 electrode;

[0066] (6) After the electrodeposition, the NiCo(OH)2 electrode sample was washed in deionized water, dried, and placed in 1 mol / L KOH for in-situ electrochemical activation for 8 cycles. The CV activation potential range was -0.5 to 0.8 V, and the scan rate was 10 mV s -1 , and obtain NiCo(OH)2 / NiCoOOH composite electrode.

[0067] A three-electrode system was adopted, with the prepared NiCo(OH)2 / NiCoOOH composite electrode as the working electrode, the Pt electrode as the counter electrode, the Hg / HgO electrode as the reference electrode, and a 1 mol / L KOH aqueous solution as the electrochemical performance test solution. The GCD curve of the electrode was tested using a CH760e electrochemical workstation.

[0068] The composite electrode was characterized by XRD after in-situ electrochemical activation. Figure 2 As shown. The diffraction peaks at 10.8° and 22.1° represent cobalt hydroxide (JPCDS.50-1891). The diffraction peaks at 33.4° and 60° represent ɑ-Ni(OH)2 (JPCDS38-0715). In addition, the diffraction peaks at 19.45°, 23.7°, and 38.4° correspond perfectly to the card of NiCoOOH (JPCDS29-0491), indicating that the electrode after in-situ electrochemical activation is a NiCo-LDH / NiCoOOH composite material.

[0069] SEM image of NiCo-LDH electrode prepared by electrodeposition Figure 3 As shown in the middle ab part, the microstructure of NiCo(OH)2 is a nanosheet structure, and it grows evenly on the graphite paper. The nanosheet retains a rich pore structure, which is beneficial to the wetting of the electrode and promotes ion transport. The EDS spectrum of the NiCo-LDH electrode shows that the Ni, Co, and O elements are evenly distributed on the electrode ( Figure 3 (Part c).

[0070] SEM images of NiCo-LDH / NiCoOOH composite electrode Figure 3 As shown in the middle part. The microscopic morphology of the electrode after in-situ electrochemical activation is also a nanosheet structure, which is also evenly distributed on the graphite paper skeleton. Compared with the unactivated sample, the thickness of the activated nanosheet becomes thinner, the wrinkles become more, and it becomes a stacked flower-like shape with a higher specific surface area. This structure is conducive to the electrolyte fully wetting the electrode to accelerate ion transfer and improve the utilization rate of active materials. The EDS energy spectrum of the NiCo-LDH / NiCoOOH composite electrode shows that the Ni, Co, and O elements are evenly distributed on the electrode ( Figure 3 (see Part f in the figure).

[0071] Example 2

[0072] A method for preparing a high-load and high-rate nickel-cobalt hydroxide supercapacitor composite electrode using a eutectic ionic liquid, specifically comprising the following steps:

[0073] (1) mixing choline chloride and urea in a molar ratio of 1:2 and stirring at 80° C. for 24 hours to obtain an ionic liquid;

[0074] (2) Weigh Ni(NO3)2 and Co(NO3)2 and dissolve them in 60 mL of the prepared ionic liquid so that the concentrations of Ni(NO3)2 and Co(NO3)2 are 0.1 mol / L, respectively. Then add 80 mL of deionized water and stir until completely dissolved to obtain an electrolyte;

[0075] (3) Cut the 1mm thick graphite sheet into 3×5cm 2 size, and then cleaned with anhydrous ethanol to obtain a graphite electrode for use;

[0076] (4) Weigh 0.4 g of tetrabutylammonium bromide and 80 ml of acetonitrile to prepare an electrode expansion solution, and then place the graphite electrode obtained in step (3) into the electrode expansion solution to expand for 10 minutes, then immerse it in deionized water for cleaning, and then dry it naturally to obtain an expanded electrode;

[0077] (5) placing the expanded electrode obtained in step (4) into the electrolyte obtained in step (2) for electrodeposition, using two parallel graphite sheets as counter electrodes, the expanded electrode as the cathode, and the reference electrode as Ag / AgCl, and performing electrodeposition at a temperature of 40° C. and a constant voltage of −1.0 V to obtain a NiCo(OH)2 electrode;

[0078] (6) After the electrodeposition, the NiCo(OH)2 electrode sample was washed in deionized water, dried, and placed in 1 mol / L KOH for in-situ electrochemical activation for 8 cycles. The CV activation potential range was -0.5 to 0.8 V, and the scan rate was 10 mV s -1 , that is, NiCo(OH)2 / NiCoOOH composite electrode.

[0079] A three-electrode system was used, with the prepared composite electrode as the working electrode, the Pt electrode as the counter electrode, the Hg / HgO electrode as the reference electrode, and a 1 mol / L KOH aqueous solution as the electrochemical performance test solution. The GCD curve of the electrode was tested using a CH760e electrochemical workstation. Figure 4 As shown, the composite electrode has a -2 The areal capacity at the current density is 3.5 mAh cm -2 , which is much larger than that of the sample deposited in water (2.1 mAh cm -2 ).

[0080] Example 3

[0081] A method for preparing a high-load and high-rate nickel-cobalt hydroxide supercapacitor composite electrode using a eutectic ionic liquid, specifically comprising the following steps:

[0082] (1) betaine and ethylene glycol were mixed in a molar ratio of 1:2 and stirred at 80° C. for 24 h to obtain an ionic liquid;

[0083] (2) Weigh Ni(NO3)2 and Co(NO3)2 and dissolve them in 60 mL of the prepared ionic liquid so that the concentrations of Ni(NO3)2 and Co(NO3)2 are 0.1 mol / L, respectively. Then, add 10 mL of deionized water and stir until completely dissolved to obtain an electrolyte;

[0084] (3) Cut the 1mm thick carbon paper into 3×5cm pieces 2 size, and then clean it with anhydrous ethanol to obtain the electrode for use;

[0085] (4) Weigh 0.4 g of tetrabutylammonium bromide and 80 ml of acetonitrile to prepare an electrode swelling solution, and then place the electrode obtained in step (3) into the electrode swelling solution to swell for 10 minutes, then immerse in deionized water for cleaning, and then naturally dry to obtain a swollen electrode;

[0086] (5) placing the expanded electrode obtained in step (4) into the electrolyte obtained in step (2) for electrodeposition, using two parallel graphite sheets as counter electrodes, the expanded electrode as the cathode, and the reference electrode as Ag / AgCl, and performing electrodeposition at a temperature of 50° C. and a constant voltage of −1.0 V to obtain a NiCo(OH)2 electrode;

[0087] (6) After the electrodeposition, the NiCo(OH)2 electrode sample was washed in deionized water, dried, and placed in 1 mol / L KOH for in-situ electrochemical activation for 16 cycles. The CV activation potential range was -0.5 to 0.8 V, and the scan rate was 10 mV s -1 , that is, NiCo(OH)2 / NiCoOOH composite electrode.

[0088] A three-electrode system was used, with the prepared composite electrode as the working electrode, the Pt electrode as the counter electrode, the Hg / HgO electrode as the reference electrode, and a 1 mol / L KOH aqueous solution as the electrochemical performance test solution. The GCD curve of the electrode was tested using a CH760e electrochemical workstation. Figure 5 As shown, the composite electrode shows high rate performance in the range of 10-100 mA cm -2The capacity retention rate under current density is 87.8%. Compared with the rate performance (43%) of the sample deposited in a pure water system under the same volume, the electrochemical performance of the electrode material prepared in the ionic liquid is greatly improved.

[0089] Comparative Example 1

[0090] A method for preparing a high-load and high-rate nickel-cobalt hydroxide supercapacitor composite electrode using a eutectic ionic liquid, specifically comprising the following steps:

[0091] (1) mixing urea, nickel chloride and cobalt chloride in a molar ratio of 1:2:2 and stirring at 80° C. for 24 hours to obtain an electrolyte;

[0092] (2) Cut the 1mm thick carbon paper into 3×5cm pieces 2 size, and then clean it with anhydrous ethanol to obtain the electrode for use;

[0093] (3) Weigh 0.4 g of tetrabutylammonium bromide and 80 ml of acetonitrile to prepare an electrode swelling solution, and then place the electrode obtained in step (2) into the electrode swelling solution to swell for 10 minutes, then immerse in deionized water for cleaning, and then dry naturally to obtain a swollen electrode;

[0094] (4) placing the expanded electrode obtained in step (3) into the electrolyte obtained in step (1) for electrodeposition, using two parallel graphite sheets as counter electrodes, the expanded electrode as the cathode, and the reference electrode as Ag / AgCl, and performing electrodeposition at a temperature of 50° C. and a constant voltage of −1.0 V;

[0095] (5) After the electrodeposition, the sample was washed in deionized water, dried, and placed in 1 mol / L KOH for in-situ electrochemical activation for 16 cycles. The CV activation potential range was -0.5 to 0.8 V, and the scan rate was 10 mV s -1 .

[0096] A three-electrode system was used, with the prepared electrode as the working electrode, the Pt electrode as the counter electrode, the Hg / HgO electrode as the reference electrode, and a 1 mol / L KOH aqueous solution as the electrochemical performance test solution. The GCD curve of the electrode was tested using a CH760e electrochemical workstation. Figure 6 As shown in Figure 2, the composite electrode shows an ultra-high loading capacity, ranging from 10 to 100 mg cm -2 The area capacity can reach 8.5 mAh cm -2 .

[0097] Comparative Example 2

[0098] A method for preparing a high-load and high-rate nickel-cobalt hydroxide supercapacitor composite electrode using a eutectic ionic liquid, specifically comprising the following steps:

[0099] (1) mixing choline chloride and urea in a molar ratio of 1:2 and stirring at 80° C. for 24 h to obtain an ionic liquid;

[0100] (2) Ni(NO3)2 and Co(NO3)2 were weighed and dissolved in 60 mL of the prepared ionic liquid so that the concentrations of Ni(NO3)2 and Co(NO3)2 were 0.1 mol / L, respectively, and 10 wt% betaine (mass concentration of betaine in the electrolyte) was added until completely dissolved to obtain an electrolyte;

[0101] (3) Cut the 1mm thick carbon paper into 3×5cm pieces 2 size, and then clean it with anhydrous ethanol to obtain the electrode for use;

[0102] (4) Weigh 0.4 g of tetrabutylammonium bromide and 80 ml of acetonitrile to prepare an electrode swelling solution, and then place the electrode obtained in step (3) into the electrode swelling solution to swell for 10 minutes, then immerse in deionized water for cleaning, and then naturally dry to obtain a swollen electrode;

[0103] (5) placing the expanded electrode obtained in step (4) into the electrolyte obtained in step (2) for electrodeposition, using two parallel graphite sheets as counter electrodes, the expanded electrode as the cathode, and the reference electrode as Ag / AgCl, at room temperature and at a constant voltage of -1.0 V for electrodeposition;

[0104] (6) After the electrodeposition, the sample was washed in deionized water, dried, and placed in 1 mol / L KOH for in-situ electrochemical activation for 8 cycles. The CV activation potential range was -0.5 to 0.8 V, and the scan rate was 10 mV s -1 .

[0105] A three-electrode system was used, with the prepared electrode as the working electrode, the Pt electrode as the counter electrode, the Hg / HgO electrode as the reference electrode, and a 1 mol / L KOH aqueous solution as the electrochemical performance test solution. The GCD curve of the electrode was tested using a CH760e electrochemical workstation. Figure 7 As shown, the composite electrode exhibits remarkable cycling stability at ultra-high loading levels.

[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode, characterized in that: The following steps are involved: A NiCo(OH)2 electrode is grown on an electrode substrate by electrodeposition, and then the NiCo(OH)2 electrode is transformed into a NiCo(OH)2 / NiCoOOH composite electrode by in-situ electrochemical activation; The electrolyte used in the electrodeposition process is obtained by mixing and dissolving nickel salt, cobalt salt and water in an ionic liquid.

2. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: The electrode substrate includes one or any combination of graphite sheet, graphite paper, carbon paper or metal substrate; The thickness of the electrode substrate is 0.1 to 5.0 mm and the area is 1 to 10 cm 2 .

3. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: The ionic liquid is one of ethylene glycol-choline chloride, urea-choline chloride, urea, ethylene glycol, betaine-ethylene glycol or urea-choline chloride-betaine.

4. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: Before the electrodeposition, the electrode substrate is immersed in a swelling liquid for swelling.

5. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 4, characterized in that: The swelling liquid is obtained by mixing tetrabutylammonium bromide and acetonitrile in a ratio of 0.4 g:80 ml; The expansion time is 2 to 60 minutes.

6. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: In the electrolyte, the concentration of nickel salt is 0.1 mol / L, the concentration of cobalt salt is 0.1 mol / L; the volume ratio of water to ionic liquid is 2:(1.5-12); The nickel salt is NiCl2, Ni(NO3)2 or NiSO4; The cobalt salt is CoCl2, Co(NO3)2 or CoSO4.

7. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: The temperature of the electrodeposition is 25-100° C., and the deposition charge is 1-150° C.

8. The method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to claim 1, characterized in that: The in-situ electrochemical activation is performed by performing CV cycles at a potential of -0.5 to 1.0 V, with a scan rate of 10 to 100 mVs -1 , the number of cycles is 1 to 100.

9. A nickel-cobalt hydroxide supercapacitor composite electrode prepared by the method for preparing a nickel-cobalt hydroxide supercapacitor composite electrode according to any one of claims 1 to 8.

10. Use of the nickel-cobalt hydroxide supercapacitor composite electrode as claimed in claim 9 in a supercapacitor.

Citation Information

Patent Citations

  • Nano-scale electrochemically expanded graphite paper conductive substrate and preparation method thereof

    CN110610814A

  • Preparation method of cathode expanded graphite paper current collector

    CN114023571A